Analysis of Fine Motor Skills in Essential Tremor: Combining Neuroimaging and Handwriting Biomarkers for Early Management - Lopez-de-Ipina, Karmele; Solé-Casals, Jordi; Sánchez-Méndez, José Ignacio; Romero-Garcia, Rafael; Fernandez, Elsa; Requejo, Catalina; Poologaindran, Anujan; Faúndez-Zanuy, Marcos; Martí-Massó, José Félix; Bergareche, Alberto; Suckling, John (Frontiers in Human Neuroscience, 2021)
Essential tremor (ET) is a highly prevalent neurological disorder characterized by action-induced tremors involving the hand, voice, head, and/or face. Importantly, hand tremor is present in nearly all forms of ET, resulting in impaired fine motor skills and diminished quality of life. To advance early diagnostic approaches for ET, automated handwriting tasks and magnetic resonance imaging (MRI) offer an opportunity to develop early essential clinical biomarkers. In this study, we present a novel approach for the early clinical diagnosis and monitoring of ET based on integrating handwriting and neuroimaging analysis. We demonstrate how the analysis of fine motor skills, as measured by an automated Archimedes’ spiral task, is correlated with neuroimaging biomarkers for ET. Together, we present a novel modeling approach that can serve as a complementary and promising support tool for the clinical diagnosis of ET and a large range of tremors.